The prospects and challenges of Kosovo's accession to the EU in light of the EU's policies and priorities - Mexhuani, Burim (Frontiers in Political Science, 2023)
Kosovo with other countries in the region, identifies unique challenges, and assesses the implications of non-recognition by five EU member states. While the EU has played a significant role in shaping Kosovo's political future, ongoing challenges such as lack of recognition and political disputes with Serbia may impact Kosovo's path towards EU accession. The paper concludes with a discussion on Kosovo's prospects for EU accession, the challenges to be addressed, and implications for the EU's credibility.